Using fecal microbiota transplantation for animal health (review) - H. Yu. Drobot; S. K. Shebeko; A. M. Ermakov (Ветеринария сегодня)
Fecal microbiota transplantation is a procedure when fecal matter from a healthy donor is administered into the intestinal tract of a recipient in order to restore microbial balance and strengthen immune responses. Mainly, fecal microbiota transplantation increases bacterial diversity and facilitates a growth in beneficial microorganisms. Thus, the procedure makes it possible to stabilize and maintain a healthy gut microbiome that inhibits the pathogen growth. In veterinary medicine, fecal microbiota transplantation is considered as a potential alternative to traditional antibiotics amid rising antibiotic resistance. Despite the lack of commonly accepted procedures, studies show that the fecal microbiota transplantation for the purposes of veterinary medicine can be used for a wide range of tasks: starting from disease prevention to immunomodulation. This review is devoted to the use of fecal microbiota transplantation for different animal species. An analysis of scientific literature suggests that most researches into the topic describe the use of fecal microbiota transplantation as a method to treat diarrhea, which is a common disorder in animals. Interestingly, the technique has been successfully used to treat canine atopic dermatitis and monitor age-related changes in fish, thus, confirming the universal nature of this procedure. There are research projects when fecal microbiota transplantation demonstrated only partial effectiveness or no effectiveness at all. Scientific evidence suggests that the effectiveness of fecal microbiota transplantation depends on the delivery route and the donor, and the first factor may have a different impact on the therapy effectiveness depending on the animal species under study. The impact of the second factor on the success of transplantation has been most widely studied for calves. Further research is needed into effects of fecal microbiota transplantation on different animals and standards need to be developed to support large-scale and safe use of the technique for animals.